622 Differences in Healthcare Resource Utilization After Surgery for Metastatic Spinal Column Tumors in Safety-Net Hospitals. (April 2023) - Elsamadicy, Aladine A.; Koo, Andrew B.; David, Wyatt; Reeves, Benjamin; Sherman, Josiah; Craft, Samuel; Hersh, Andrew; Duvall, Julia; Lo, Sheng-fu; Shin, John H.; Mendel, Ehud; Sciubba, Daniel M.
Abstract : INTRODUCTION: Safety Net Hospitals (SNH) are those which serve an especially high proportion of Medicaid, uninsured, and charity care patients, though few have studied the impact of SNH status on healthcare resource utilization for patients with metastatic spinal column tumors. METHODS: A retrospective cohort study was performed using the 2016-2019 National Inpatient Sample database. Adult patients undergoing surgery for metastatic spinal column tumors were identified using ICD-10-CM codes. Admissions were dichotomized by SNH status, defined as the top quartile of Medicaid and uninsured burden. Hospital characteristics, patient demographics, comorbidities, intraoperative variables, and outcomes were assessed. Multivariate logistic regression analyses were used to identify predictors of extended LOS, non-routine discharge, and increased cost. RESULTS: Of the 11, 505 patients identified, 24.0% (n = 2, 760) were treated at a SNH and 76.0% (n = 8, 745) were treated at a Non-SNH (N-SNH). Compared to patients treated at N-SNH, a greater proportion of patients at SNH were African American, male, and of lower income quartile. Number of comorbidities (p = 0.324), intraoperative complications (p = 0.488) and postoperative complications (p = 0.064) were similar between cohorts. Patients treated at SNH typically experienced greater LOS (SNH: 12.3 ± 11.3 days vs. N-SNH: 10.1 ± 9.5 days, p<0.001), though total cost of admission (SNH: $58, 804 ± 39, 088 vs. N-SNH: $54, 569 ± 36, 781, p = 0.550), non-routine discharge disposition (SNH: 48.2% vs. N-SNH: 48.4%, p = 0.715) and mortality rate (SNH: 3.1% vs. N-SNH: 2.7%, p = 0.629) were similar. On multivariate analysis, SNH status independently predicted extended LOS [OR: 1.41, p = 0.009], but not non-routine discharge [OR: 0.97, p = 0.773] or increased cost [OR: 0.93, p = 0.655]. CONCLUSIONS: Our study suggests that the quality of care provided by SNH is largely similar to that provided by non-SNH for patients undergoing surgical intervention of metastatic spinal column tumors